ICT entertainment appliances' impact on domestic electricity consumption. (March 2017) - Pothitou, Mary; Hanna, Richard F.; Chalvatzis, Konstantinos J.
Abstract: Increased electricity consumption and environmental impacts of Information Communication Technology (ICT) have been subjects of research since the 1990s. This paper focuses on consumer electronics in households, in particular TVs, computers and their peripherals. ICT accounts for almost 15% of global domestic electricity use, including waste energy from devices left on standby which is estimated in the EU-27 to contribute 6% of residential energy demand. In Europe, the household electricity consumption from small electronic appliances, including ICT, increased by 2.5 times in 2011 compared to 1990. Similarly, in the UK, energy demand from electronic devices accounted for 23% of total household electricity use in 2012, compared to 12% in 1990. This is an outcome of the market saturation of new, cheaper ICT entertainment devices, facilitated by marketing strategies which identify new needs for consumers, as charted by the review of market growth in this paper. New increasingly portable laptops, smart phones and tablets with wireless connectivity allow householders to perform a wider range of activities in a wider range of locations throughout the home, such as social networking while the television is active. We suggest that policies which consider how to increase the energy efficiency of ICT devices alone are unlikely to be successful since effective strategies need to address how the drivers which have developed around the use of ICT can be adapted in order to conserve electricity in households. A range of policy solutions are discussed, including feedback, public information campaigns, environmental education, energy labelling, bans of, or taxation on the least efficient products as well as the use of a TV as central hub to perform the existing functions of multiple devices.